The Quality of Graduate Students as Thai Qualifications Framework for Higher Education, Boromarajonani College of Nursing, Sawanpracharuk Nakhonsawan - บุญประเสริฐ นภัสวรรณ; วิทยโชคกิติคุณ นิรนาท; เอกลัคณารัตน์ ศรีสุดา; สินาคม ธีริศา (Ganesha Journal, 2019)
This descriptive research aimed to study the quality of graduate students as Thai Qualifications Framework for Higher Education for Graduate students of Boromarajonani Nursing College, Sawanpracharak, Nakhonsawan. The samples were primary supervisors of graduates who graduated in the academic year 2017. The research instruments was questionnaire about the quality of graduates according to the national higher education qualifications framework. Data analysis was calculated by percentage, mean, standard deviation. The results of the study found that: graduate quality according to the mean of overall standard of higher education qualifications in nursing science was at a high level (m= 3.98, s= 0.55) when considering each aspects found that the highest mean was moral and ethical skills at a high level (m =4.19, s = 0.58), followed by mean of interpersonal relationships and responsibilities at a high level (m = 4.14, s = 0.57), and the lowest mean was knowledge at a high level (m=3.84, s = 0.48)